Developing brain and general anesthesia – is there a cause for concern? - Jevtovic-Todorovic, Vesna (Medicine Reports Ltd, 2010)
Skilled management of sick premature babies and very young children has resulted in numerous exposures of their brains to a variety of anesthetic agents designed to achieve the substantial depth of neuronal inhibition required for complete loss of consciousness and insensitivity to pain. Unfortunately, our recent animal findings suggest that commonly used general anesthetics are damaging to developing neurons and cause significant neuronal deletion in vulnerable brain regions. In addition, emerging animal and human data suggest an association between early exposure to general anesthesia and long-term impairment of cognitive development. Consequently, the prudence of frequent anesthesia exposure of this population is now being scrutinized. It is important to note that on the basis of currently available information, there are still considerable differences of opinion regarding the clinical relevance of the animal findings. Since there is insufficient evidence establishing a clear association between animal and human findings, it would be premature to suggest major changes in current clinical practice.